2015
DOI: 10.3389/fpsyt.2015.00022
|View full text |Cite
|
Sign up to set email alerts
|

Radio Electric Asymmetric Conveyer: A Novel Neuromodulation Technology in Alzheimer’s and Other Neurodegenerative Diseases

Abstract: Global research in the field of pharmacology has not yet found effective drugs to treat Alzheimer’s disease (AD). Thus, alternative therapeutic strategies are under investigation, such as neurostimulation by physical means. Radio electric asymmetric conveyer (REAC) is one of these technologies and has, until now, been used in clinical studies on several psychiatric and neurological disorders with encouraging results in the absence of side effects. Moreover, studies at the cellular level have shown that REAC te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Besides the clinical involvements of the CF as neuroimaging biomarker, the fundamental assumptions on which the method is based could shed new insights in the comprehension of AD (Rinaldi et al, 2015 ). The integration of information represents one of the most important information processing stage of the brain and aberrations of information integration are reported in a plethora of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the clinical involvements of the CF as neuroimaging biomarker, the fundamental assumptions on which the method is based could shed new insights in the comprehension of AD (Rinaldi et al, 2015 ). The integration of information represents one of the most important information processing stage of the brain and aberrations of information integration are reported in a plethora of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The REAC is a technology platform for biomodulation [ 35 , 41 ] and neuromodulation [ 20 , 24 , 33 ] treatments. The REAC technology device used in this clinical investigation was a BENE 110 model (ASMED, Florence, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…In the field of biomodulation, specific tissue optimization (TO) treatment protocols with REAC technology are effective not only in post-traumatic outcomes [ 25 , 26 ], regenerative medicine [ 27 , 28 , 29 ], and in neurodegenerative diseases [ 30 , 31 , 32 , 33 ], but also in direct cellular reprogramming [ 34 , 35 , 36 ]. TO treatments have been used for years, both in human and veterinary medicine, in the treatment of post-traumatic lesions in various types of tissues, as muscle, ligament and tendon; nevertheless, scientific work on this topic had never been produced to date.…”
Section: Introductionmentioning
confidence: 99%
“…The REAC is an innovative patented technology9,10 for biostimulation and/or bioenhancement that induces weak radioelectric currents in tissue, to induce cell-reprogramming activity 12. The model used in this study (BENE Bio Enhancer – Neuro Enhancer ® ; ASMED, Florence, Italy) is specifically designed for regenerative treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of a tool capable of counteracting the cartilage degeneration occurring during OA without side effects could represent an interesting approach in OA therapy. In this regard, we have recently observed that Regenerative Tissue Optimization (TO-RGN) treatment with radioelectric asymmetric conveyer (REAC) technology9,10 significantly influenced the differentiation capability of mouse embryonic stem cells11 as well as the pluripotency and plasticity of human skin-derived fibroblasts 12. These findings have suggested the purpose of this study – to clarify whether the positive effect of REAC TO-RGN might be related to a capability to counteract the IL-1β-induced signaling pathway, a primary cause of OA.…”
Section: Introductionmentioning
confidence: 99%